Implementasi Algoritma Line Mapping Dengan Sensor Ultrasonik Pada Robot Pengantar Makanan Berbasis Mikrokontroler - Nirwan Sinuhaji; Dewi Yohana br Ginting; Benar (Bulletin of Computer Science Research, 2023)
The development Of the world of robotics at thi time in the current era of industrial technology robotics technology is able to improve the quality and quantity of production in various factories so that naby new ideas emerge about robotics technology that are useful for human life. By utilizing robotic, especially in restaurants or restaurants, it can already be done restaurants or restaurants, it can already be done without using human hands, but it has been done with robotic technology. A line follower food delivery robot which is a type of moving robot using an ATMega16 microcontroller whose mission is to detect and follow a guide line that has been made on the track field. In the research algorithm used line mapping. This robot still uses a permanent arm, and this robot cannot automatically pick up or place food at its destination